CORPORATE GOVERNANCE IMPACT ON INDONESIAN BANK FINANCIAL PERFORMANCE EXCELLENCE - Riyadhi Saputra, Muhammad; Andueriganta Fadhlihi; Arifin, Arifin (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2025)
Good Corporate Governance (GCG) has become increasingly important in the financial performance of companies because sound governance functions as an internal and external control mechanism that ensures companies operate in a healthy, transparent manner, and are oriented towards the interests of all stakeholders. This research aims to examine journal papers that discuss how Good Corporate Governance will influence the financial performance of banking institutions. This study employs the systematic literature review (SLR) method with samples consisting of secondary data from various journal publications that have been collected through the Google Scholar database. The journals used as data in this research are publications released from 2021-2025 that investigate the influence of GCG on banking financial performance. The results of the research employing systematic literature review demonstrate that GCG's impact on financial performance is dependent on several aspects, namely the method of drawing conclusions (partial and simultaneous), the proxy variables employed, the control variables utilized, and the differences in the time periods used by researchers.